Identificación por inmunofluorescencia de citoqueratinas 8, 13, 19, desmoplaquina y desmogleína en células madre de la papila apical. ex vivo. Prueba piloto. (2020)
The stem cells of the apical papilla have excellent properties of differentiation and great potential for use in tissue engineering protocols, without However, the potential for epithelial differentiation has not been explored with this cell type. The objective is to analyze the expression of cytokeratins 8, 13, and 19, desmoplaquine and desmoglein by immunofluorescence. Materials and Methods: Apical papilla tissue cell cultures were performed using Explant technique of healthy donor patients. Characterization was performed cell by flow cytometry, was analyzed by immunofluorescence the expression of cytokeratins 8, 13 and 19, desmoplakine and desmoglein. Results: The cells of the apical papilla expressed cytokeratin 8, 13 and 19 desmoplaquine and desmoglein, observed through the immunofluorescence technique, which was applied to the cells of the fourth pass that demonstrated a cell viability of 86.76% by means of cytometry of flow and trypan blue. Conclusions: The stem cells of the apical papilla express epithelial markers and support the idea that they could be used as an alternative source to develop artificial oral mucosa protocols.